Keterkaitan Partisipasi Masyarakat terhadap Kesuksesan Pelaksanaan Kegiatan Daerah Pangan Mandiri di Kecamatan Kebasen Kabupaten Banyumas - Wibowo, Karist Dwi; Kadafi, Muamar (AGRITEXTS: Journal of Agricultural Extension, 2023)
Independent food area activities describe activities to empower communities against food resistance. Community participation is needed to enable people to achieve success in activities. This study aims to see the extent of community participation in independent food areas and the level of success of independent food areas, as well as examine the relationship between the level of participation and the success of independent food areas. This study design uses a quantitative approach. This assessment technique applies survey techniques and uses questionnaires. The study location was chosen purposively in Adisana Village, Kebasen Sub-district, Banyumas Regency. The sampling technique used was probability sampling, using the method of saturated sampling (census) of 60 people. The analysis tool uses descriptive analysis and Rank Spearman Correlation statistical analysis. This study shows that (1) the community is actively implementing “pangan mandiri” at the stage of enjoying the benefits; (2) obtained a correlation between the stages of participation and independent food activities. This research concludes that the participation stages at each stage are actively involved in the success of independent food activities. There is a correlation between the level of community involvement and the success of independent food activities. Implementing this study activity will likely lead to increased support for independent food initiatives, thereby facilitating the further development of independent food areas.